Distribution and Reactivity of Gallates Toward Galvinoxyl Radicals in Sds Micellar Solutions - Effect of the Alkyl Chain Length - Lissi-Gervaso, E; Aspee-Lamas, A; Aliaga-Vidal, C; Aliaga-Vidal, C; Abuin-Saccomano, E (2011)
Sin Editorial Disponible